Effect of Closure of Anterior Abdominal Wall Layers on Early Postoperative Findings at Cesarean Section: A Prospective Cross-sectional Study - Ersin Çintesun; Ayşe Gül Kebapçılar; Mustafa Gazi Uçar; Setenay Arzu Yılmaz; Mete Bertizlioğlu; Çetin ÇELİK; Özlem Seçilmiş Kerimoğlu (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2021)
Abstract Objective To investigate the effect of closure types of the anterior abdominal wall layers in cesarean section (CS) surgery on early postoperative findings. Methods The present study was designed as a prospective cross-sectional study and was conducted at a university hospital between October 2018 and February 2019. A total of 180 patients who underwent CS for various reasons were enrolled in the study. Each patient was randomly assigned to one of three groups: Both parietal peritoneum and rectus abdominis muscle left open (group 1), parietal peritoneum closure only (group 2), and closure of the parietal peritoneum and reapproximation of rectus muscle (group 3). All patients were compared in terms of postoperative pain scores (while lying down and duringmobilization), analgesia requirement, and return of bowel motility. Results The postoperative pain scores were similar at the 2nd, 6th, 12th, and 18th hours while lying down. During mobilization, the postoperative pain scores at 6 and 12 hours were significantly higher in group 2 than in group 3. Diclofenac use was significantly higher in patients in group 1 than in those in group 2. Meperidine requirements were similar among the groups. There was no difference between the groups' first flatus and stool passage times. Conclusion In the group with only parietal peritoneum closure, the pain scores at the 6th and 12th hours were higher. Rectus abdominismuscle reapproximations were found not to increase the pain score. The closure of the anterior abdominal wall had no effect on the return of bowel motility.